Pazopanib for metastatic soft-tissue sarcoma: A multicenter retrospective study. (April 2021) - Koca, Sinan; Beşiroğlu, Mehmet; Özçelik, Melike; Karaca, Mustafa; Bilici, Mehmet; Hacıoğlu, Bekir; Doğu, Gamze G; Kaplan, Nihal B; Oruç, Zeynep; Aydın, Dinçer; Dane, Faysal
Purpose: Soft tissue sarcomas are associated with a poor prognosis and low chemotherapeutic efficiency. Pazopanib is an orally available multi-tyrosine kinase inhibitor that was explored in patients with non-adipocytic advanced soft tissue sarcomas. The aim of this retrospective study was to evaluate the real life data of single-agent pazopanib efficacy and safety for soft tissue sarcomas in the Turkish population. Materials and methods: We evaluated a total of 103 patients (41 males, 62 females) who received pazopanib for advanced non-adipocytic soft tissue sarcomas diagnosis in eight centers of Turkey, retrospectively. The pazopanib dose was 800 mg once daily. Progression-free survival, overall survival, and adverse events were analyzed. Results: The median age was 50 years (range, 38–58). Majority of the patients had leimyosarcoma (41%). Median progression-free survival was 4.3 months, and the median overall survival was 10.1 months. The main common toxicities were fatigue, anorexia, weight loss, nausea, hypertension, and grade ≥3 toxicities were fatigue, anorexia, weight loss, and liver disorder. Conclusion: Pazopanib is an efficient and tolerable agent and is well tolerated in good performance status patients with relapsed, advanced non-adipocytic soft tissue sarcomas.